Aptamer and Oligonucleotide-Based Biosensors for Health Applications - Beatriz Mayol; I. Zeina Qubbaj; Julieta Nava-Granados; Katherine Vasquez; Scott T. Keene; Juliane R. Sempionatto (Biosensors)
Aptamers have emerged as powerful molecular recognition elements for biosensing applications, offering high specificity, stability, and adaptability. This review explores key considerations in designing aptamer-based sensors (aptasensors), with a focus on biomarker selection, aptamer design, and detection and immobilization strategies. However, challenges such as biofluid stability and reversibility must be addressed to improve biosensor performance. In this study, the potential of aptamer-based platforms in diagnostics is explored, emphasizing their advantages and future applications. Looking ahead, advances in multifunctional aptamers, integration with nanomaterials, and computational optimization are highlighted as promising directions for enhancing their effectiveness in biosensing.